Effect of wheat residue management practices and nitrogen rates on productivity and nutrient uptake of rice (Oryza sativa)-wheat (Triticum aestivum) cropping system - SINGH, MAHENDER; SHARMA, S N (The Indian Journal of Agricultural Sciences, 2013)
Experiments were conducted during 1994-95 to 1995-96 to study the effect of residue management practices and nitrogen rates in rice-wheat cropping system. Wheat (Triticum aestivum L. emend. Fiori & Paol.) residue incorporation with no nitrogen or inadequate nitrogen (60 kg N/ha) had an adverse effect on productivity and nutrient uptake of ricewheat cropping system. When adequate nitrogen (180 kg N/ha) was applied, residue incorporation increased productivity and nutrient uptake over both residue removal and residue burning, the latter two residue management practices were at par at all the rates of N application. At 180 kg N/ha residue incorporation gave 0.4-0.7 tonne/ha more grain and uptake of 40-65 kg/ha more NPK in rice-wheat system compared with the other two residue management practices. Residue incorporation also resulted in more recovery of fertilizer N by rice and had a significant residual effect on succeeding wheat. It, thus, indicates that fertilizer nitrogen with residue incorporation was conserved and better utilized by rice and succeeding wheat.